Trusting the Threads: How Brand and Quality Weave Purchase Decisions at Griya Batik Semarangan - Firdaus; Callista Cahya Waroka; Edy Purwanto; Amrudin Mahfud Jumai (IECON: International Economics and Business Conference, 2025)
This study aims to analyze the effect of brand image and product quality on consumer purchase intention toward Griya Batik Semarangan, with brand trust as a mediating variable. The research is motivated by the growing competition in the traditional fashion industry, especially among local batik producers, which requires a deeper understanding of consumer behavior and decision-making factors. A quantitative approach was employed, using a survey method by distributing questionnaires to 100 respondents who are consumers of Griya Batik Semarangan. The data were analyzed using Partial Least Squares (PLS) with the assistance of SmartPLS 4 software. The findings reveal that both brand image and product quality have a positive and significant influence on purchase intention, as well as on brand trust. However, brand trust does not have a significant effect on purchase intention and fails to mediate the relationship between brand image or product quality and purchase intention. These results suggest that while brand image and product quality are important in building consumer trust, brand trust is not the dominant factor driving purchase intention in the case of Griya Batik Semarangan. The study contributes to the literature on consumer behavior in local cultural products and provides practical implications for traditional fashion businesses in enhancing their market strategies.